Exact fuzzy observer for a baker’s yeast fermentation process - Herrera, Enrique (2007)
The purpose of this work is to design an exact fuzzy observer for a bioprocess switching between two different metabolic states. A continuous baker’s yeast culture is divided in two sub-models: a respiro fermentative with ethanol production and a respirative with ethanol consumption. An exact fuzzy observer model using sector nonlinearity was built for both nonlinear models; the observer gains were designed using Linear Matrix Inequalities (LMI’s). The observer premise variables depend on the state variables estimated by the fuzzy observer.